Utilization Of Instagram Reels Features As A Digital Marketing Strategy At Affection Organizer - Putri, Siti Lindy Sistiana; Khoirotunnisa, Fani (Jurnal Ekonomi, Manajemen dan Akuntansi (JEKMA), 2025)
The development of digital marketing has encouraged businesses to adapt the use of short-form video content on social media platforms, particularly through Instagram Reels. Affection Organizer, as an event organizing service company, utilizes this feature to enhance brand awareness and audience engagement. This study aims to examine the use of Instagram Reels as a digital marketing strategy at Affection Organizer and to analyze its effectiveness in attracting potential clients. The research employs a descriptive qualitative approach using purposive sampling, involving three key informants from the marketing division. Data were collected through in-depth interviews focusing on content production processes, applied visual concepts, and audience responses to Reels content. The findings indicate that Instagram Reels is able to represent event atmospheres more authentically and emotionally compared to photo-based content, thereby fostering psychological closeness between the brand and its audience. Furthermore, Reels is considered effective as it aligns with the preferences of consumers of productive age who tend to favor dynamic, aesthetic, and storytelling-oriented visual content. The main challenges identified include the need for continuous creativity and relatively time-consuming content production. Therefore, it can be concluded that Instagram Reels is an effective digital marketing strategy for increasing visibility and attracting potential clients to Affection Organizer.